2023
DOI: 10.1021/acsomega.2c07719
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Based Materials for Wastewater Treatment: Superior Adsorbent Materials for the Removal of Hazardous Pollutants

Abstract: In previous years, different pollutants, for example, organic dyes, antibiotics, heavy metals, pharmaceuticals, and agricultural pollutants, have been of note to the water enterprise due to their insufficient reduction during standard water and wastewater processing methods. MOFs have been found to have potential toward wastewater management. This Review focused on the synthesis process (such as traditional, electrochemical, microwave, sonochemical, mechanochemical, and continuous-flow spray-drying method) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 209 publications
0
32
0
Order By: Relevance
“…Recently, Thakur and team highlighted the synthesis and active mechanism of function of advanced MOFs as adsorbents for the removal of hazardous pollutants under different environmental conditions. 19 Xia and group developed three Zr-based MOFs with different topologies and pore sizes for the removal of tetracycline and studied their kinetics and mechanism in detail. 20 MOFs have developed into next-generation utility materials due to their versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Thakur and team highlighted the synthesis and active mechanism of function of advanced MOFs as adsorbents for the removal of hazardous pollutants under different environmental conditions. 19 Xia and group developed three Zr-based MOFs with different topologies and pore sizes for the removal of tetracycline and studied their kinetics and mechanism in detail. 20 MOFs have developed into next-generation utility materials due to their versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic interactions between the MOFs and pollutants are favored by protonation and deprotonation, which is caused by net surface charges. Similarly, studies have shown that MOFs contain −OH groups and forms H-bonds with pollutants . Moreover, the adsorption of pollutants is relatively easier by MOFs’ relatively larger surface areas .…”
Section: Innovative Materials For Wastewater Treatmentmentioning
confidence: 99%
“…Various synthesis methods are used for producing the different types of MOF structures, which include the diffusion method, the sonochemical method, the hydro­(solvo)­thermal method, the microwave method, the electrochemical method, and the mechanochemical method. , The synthesis methods have been discussed extensively by Wang et al. in 2022 and Kaur et al in 2023. , The benefits and drawbacks of various synthesis processes are discussed in Table .…”
Section: Metal–organic Framework As Catalysts For Pms/ps Activationmentioning
confidence: 99%
“…Zeolitic imidazolate frameworks (ZIF) are created by metal ions (Co, Zn, Fe, Cu, etc.) and imidazole derivatives and are topologically structured zeolites . The properties through which the catalytic activity is enhanced are surface sensitivity, large surface area, large pore size, and thermal stability, among others. Furthermore, the unique structural properties of ZIF-MOFs allow for a high degree of control over the catalytic performance, allowing for material tailoring for specific applications. ,, There are many different types of ZIFs, which can be classified based on the type of metal ion or cluster used in their construction, the type of organic ligand used, and their pore size and shape. , The different types of metal linkers used are 2-nitroimidazole, 2-methylimidazole, benzimidazole, and metronidazole, and the metal oxides are Co 3 O 4 , ZnCoO X , ZnO, and CoS, as mentioned in Table .…”
Section: Metal–organic Framework As Catalysts For Pms/ps Activationmentioning
confidence: 99%
See 1 more Smart Citation